Determination of permissible alcohol and vinegar in Shariah and scientific perspectives - Jamaluddin, Mohammad Aizat; Mat Hashim, Dzulkifly; Abdul Rahman, Russly; Ramli, Mohd Anuar; Ab. Majid, Mahmood Zuhdi; Othman, Rashidi; Amin, A. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
The halal food production industry is gaining greater attention among Muslim and non-Muslim majority countries, particularly due to the increase of global market demand. One of the critical areas in issuing halal certified food is the determination of allowable alcohol content in food and drinks. The level of alcohol content has not standardized in several standards and fatwa of Islamic scholars. In Islam, the alcohol in several fruit products is produced through fermentation process such as takhammur (wine making) and takhallul (vinegar making). The fermentation process gives an impact to the status of the food products either permissible or prohibited. Therefore, the purpose of this paper is to discuss on the determination of permissible alcohol and vinegar by fermentation process content in selected food products from Shariah and science perspectives. In doing so, the views of authentic of Islamic Law in this issue are supported by lab work approached. As a result, in the first phase there are three types of by products from takhammur, while two types of takhallul. All the products can be determine of the alcohol content and give an implication of the status either permissible (halal) or prohibited (haram). Hence, in juice considered as halal due to lower of alcohol content. While cider or alcoholic beverage is haram due to above alcohol level permitted which is above of the 1%. Besides, cider vinegar or vinegar is halal by the interpretation of hadith of permissible conversion from alcoholic to vinegar itself.